American Footprints and Fault Lines in the World (Journal of Asian Development Studies, 2013)
The purpose of writing this paper is to analyze the American role in world politics. The intention behind writing this paper is to analyze the factors which forced America to go on the back foot and to see what faults and mistakes were committed by America since its birth and especially after assuming the role of sole super power of the world which will help us to understand its policies and the objectives of American government regarding the rest of the world. American after assuming the role of a superpower committed many faults throughout its history and still it is committing lot of faults which will ultimately result in the shape of loosing of friend after friend in the world and it appeared as a unreliable friend for its allies and for the developing countries like Pakistan who mostly depended upon its assistance for their developmental program. This paper enables us to understand the faults which America committed throughout its history and due to which its popularity declined. America lost its creditability due to its fault line in the world. Primary and secondary sources were collected and then content analysis was made to write this paper.